Evolutionary relationships in Panicoid grasses based on plastome phylogenomics (Panicoideae; Poaceae). Issue 1 (December 2016) - Burke, Sean; Wysocki, William; Zuloaga, Fernando; Craine, Joseph; Pires, J.; Edger, Patrick; Mayfield-Jones, Dustin; Clark, Lynn; Kelchner, Scot; Duvall, Melvin
Abstract Background Panicoideae are the second largest subfamily in Poaceae (grass family), with 212 genera and approximately 3316 species. Previous studies have begun to reveal relationships within the subfamily, but largely lack resolution and/or robust support for certain tribal and subtribal groups. This study aims to resolve these relationships, as well as characterize a putative mitochondrial insert in one linage. Results 35 newly sequenced Panicoideae plastomes were combined in a phylogenomic study with 37 other species: 15 Panicoideae and 22 from outgroups. A robust Panicoideae topology largely congruent with previous studies was obtained, but with some incongruences with previously reported subtribal relationships. A mitochondrial DNA (mtDNA) to plastid DNA (ptDNA) transfer was discovered in thePaspalum lineage. Conclusions The phylogenomic analysis returned a topology that largely supports previous studies. Five previously recognized subtribes appear on the topology to be non-monophyletic. Additionally, evidence for mtDNA to ptDNA transfer was identified in bothPaspalum fimbriatum andP. dilatatum, and suggests a single rare event that took place in a common progenitor. Finally, the framework from this study can guide larger whole plastome sampling to discern the relationships in Cyperochloeae, Steyermarkochloeae, Gynerieae, and otherincertae sedis taxa that are weakly supported or unresolved.